FACTORS AFFECTING THE WAREHOUSES LOCATION WITH ACCENT ON COMMUNICATION WITH THE EXTERN ENTITIES - Chocholáč, Jan; Hrdý, David; Kuptcova, Anastasiia; Průša, Petr (Vysoká škola technická a ekonomická v Českých Budějovicích, 2016)
This paper deals with the factors influencing the new warehouse location with accent on necessary communication with the external entities. The objective is to perform, based on the statistics of the World Bank, the comprehensive comparison of this indicator in terms of individual countries and to declare where is what level of administrative burden and necessary communications with the external entities. This indicator may be one of the key factors in the matter of new warehouse location, by which the prospective investor will decide where its business plan will be implemented.
Faktory ovlivňující lokaci skladu s akcentem na komunikaci s externími subjekty
Keywords: warehouse location; communication; extern entities; lokace skladů; komunikace; externí subjekty